Detecting Emotion in Speech: Validating a Remote Assessment Tool. Issue 3 (2nd October 2022) - Dor, Yehuda I.; Algom, Daniel; Shakuf, Vered; Ben-David, Boaz M.
ABSTRACT: Recent global events have called for the development of online testing and evaluation techniques, for both clinical and research purposes. Online testing is especially important for older adults who might have limited access to health services due to mobility difficulties or health risks. The current study aimed to validate an online tool, Internet-based Test for Rating of Emotions in Speech (iT-RES), designed to test the perception of emotions in spoken language and assess its efficacy as a remote telehealth assessment tool for older adults. Forty-one older adults (age 60–80) and 44 young adults (age 20–29) performed the online iT-RES. Age-related differences in the online tool were compared with respective age-related effects in a parallel lab-based tool. The three main age-related effects found in the lab-based version were replicated in the iT-RES online version. (1) Better identification of emotion by young adults; (2) Failures of Selective Attention were larger for older adults; (3) Older adults gave lower weight to the prosodic channel as compared to younger adults. Our findings add to the growing body of literature regarding the validity of online neuropsychological assessment. We also present and discuss several measures taken to ensure quality online testing and increase overall test validity.